2000
DOI: 10.1007/s101520050004
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between macro-algal mats and invertebrates in the Ythan estuary, Aberdeenshire, Scotland

Abstract: Blooms of opportunistic green macro-algae are a common feature of coastal areas and their effects on mudflat invertebrates can be dramatic. On the Ythan estuary, Aberdeenshire, Scotland, we have carried out a number of manipulative field experiments designed to evaluate the effects on invertebrates of different species of macro-algae with contrasting ecologies, and the effects of invertebrates on the development of the blooms. Macro-algal mats were found to have dramatic negative effects on the density of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 12 publications
4
58
0
1
Order By: Relevance
“…This is mainly related to increased eutrophication. Similar algal mat blooms have been experienced along the east coast of Great Britain (Raffaelli 2000) and may have been accompanied there by similar increases in N. diversicolor abundance. No historical data are available for the site at Hamford Water in the present study, but it is tentatively suggested that increases in N. diversicolor abundance around the south-east coast of England and those countries bordering the southern North Sea are not unlikely.…”
Section: Laboratory Studiessupporting
confidence: 57%
“…This is mainly related to increased eutrophication. Similar algal mat blooms have been experienced along the east coast of Great Britain (Raffaelli 2000) and may have been accompanied there by similar increases in N. diversicolor abundance. No historical data are available for the site at Hamford Water in the present study, but it is tentatively suggested that increases in N. diversicolor abundance around the south-east coast of England and those countries bordering the southern North Sea are not unlikely.…”
Section: Laboratory Studiessupporting
confidence: 57%
“…Previous studies have suggested that the most relevant ecological relation between green macroalgae and the macroepifaunal community may be of a non-trophic nature, and based instead, on protection offered by the mats against predation (Aníbal, 1998). This hypothesis has also been described elsewhere (Thiel and Reise, 1993;Raffaelli, 2000). However, few studies have focused on the influence of surface morphological features on community structure associated with macroalgal blooms in tidal flats.…”
Section: Introductionsupporting
confidence: 58%
“…The deleterious effects these blooms have on the surrounding system while alive and following die-off have been studied extensively (e.g. Sfriso et al 1992, Raffaelli 2000, Hauxwell et al 2001, Cummins et al 2004, Nuzzi & Waters 2004.…”
Section: Introductionmentioning
confidence: 99%